Cryptic metasomatism revealed by Li isotopes of mantle xenoliths beneath the Thrace Basin, NW Turkey. (15th October 2018) - Jing, Jie-Jun; Su, Ben-Xun; Xiao, Yan; Martin, Laure; Zhang, Hong-Fu; Uysal, İbrahim; Chen, Chen; Lin, Wei; Chu, Yang; Seitz, Hans-Michael; Zhang, Peng-Fei
Graphical abstract: Highlights: Silicate melt metasomatism and recent fluid metasomatism were revealed by Li isotope systematics. Silicate melts from dehydrated slab and subduction-related fluids are inferred as metasomatic melts and fluids. Lithium isotope systematics are sensitive to cryptic metasomatism. Abstract: To identify metasomatic overprints in the mantle xenoliths from the Tethys orogenic belt in NW Turkey, we report here in situ Li concentrations and isotopic compositions of olivine, clinopyroxene and orthopyroxene along with major element compositions of minerals, and whole-rock trace element compositions of the mantle xenoliths composed of refractory harzburgites with subordinate lherzolites and one olivine-websterite. Their non-depleted whole-rock light rare earth element (LREE) patterns, enrichment in large ion lithophile elements and depletion of high field strength elements, imply subduction-related metasomatism, while the Y-depletion may indicate the derivation of the metasomatic melts/fluids from a garnet-bearing source. Minerals from all the xenoliths display homogeneous major element compositions, however they show large intra- and inter-mineral Li elemental and isotopic variations. The Li contents of olivines range from 1.45 to 2.81 ppm with large variations in δ 7 Li values (+1.2 to +17.5‰). The orthopyroxenes have variable Li contents (0.07–16.6 ppm) and δ 7 Li values (−71.6 to +10.8‰), with higher Li contents and lower δ 7 Li values in their cores. The clinopyroxenes show variable Li contents (2.16–22.0 ppm) and δ 7 Li values (−54.6 to +1.9‰), with commonly higher Li contents and lower δ 7 Li values in their cores. The Li-isotopic zonation observed in most pyroxene grains is most likely a recent overprint of subduction-related fluids. By contrast, olivines with fairly homogeneous low Li contents compared to pyroxenes appear to be less affected by the metasomatic melts/fluids. The correlation between δ 7 Li values and the forsterite contents of olivines, along with the preferential uptake of Li in pyroxenes, and the presence of light Li isotopic compositions in the cores of pyroxenes, indicate the influence of silicate melt-rock interaction. We interpret these results as evidence for a metasomatic overprint predating the zonation in the Tethys orogenic belt of NW Turkey. Thus, both the recent fluid metasomatism and earlier silicate melt metasomatism are strongly related with the successive subduction of the Tethyan oceanic plate.